Candida tropicalis ZD-3 prevents excessive fat deposition by regulating ileal microbiota and bile acids enterohepatic circulation in broilers - Feng, Jiaqi; Wang, Fang; Nan, Shanshan; Dou, Lijing; Pang, Xiaotong; Niu, Junli; Zhang, Wenju; Nie, Cunxi (Frontiers in Microbiology, 2024)
Evidence suggests that the dietary intake of Candida tropicalis ZD-3 (ZD-3) has various health benefits, but the treatment mechanisms and effects remain unclear. The aim of this study investigates the effect of ZD-3 on reducing fat deposition in broilers and the underlying mechanism. 180 one-dayold, yellow-feathered broilers were randomly divided into three groups: control (CON) group fed a basal diet, an active Candida tropicalis ZD-3 (ZD) group supplemented with ZD, and a heatinactivated Candida tropicalis ZD-3 (HZD) group supplemented with HZD. The experiment lasted for 28 d. The ZD and HZD treatments significantly reduced the abdominal fat index (P < 0.05), decreased TG levels in serum and liver (P < 0.05), altered the ileal microbial composition by reducing the Firmicutes to Bacteroidetes (F/B) ratio. Additionally, the ZD and HZD treatments reduced liver cholesterol by decreasing ileal FXR-FGF19 signaling and increasing liver FXR-SHP signaling (P < 0.05). The ZD and HZD treatments also changed liver PC and TG classes lipid composition, regulating liver lipid metabolism by promoting TG degradation and modulating the signal transduction of the cell membrane. Overall, ZD-3 was effective in improving lipid metabolism in broilers by regulating the ileal microbial composition and BAs enterohepatic circulation. This study provides a theoretical basis for the development and application of ZD-3 for the regulation of lipid metabolism in broilers.